A physical activity program is no more effective than standard care at maintaining upper limb activity in community-dwelling people with stroke: secondary outcomes from a randomized trial. (October 2019) - Langhammer, Birgitta; Ada, Louise; Gunnes, Mari; Ihle-Hansen, Hege; Indredavik, Bent; Askim, Torunn
Objective: To evaluate whether an 18-month, physical activity coaching program is more effective than standard care in terms of upper-limb activity. Design: A prospective, randomized controlled trial. Setting: Three municipalities in Norway. Population: A total of 380 persons with stroke. Intervention: The intervention group received follow-up visits and coaching on physical activity and exercise each month for 18 months after inclusion, by a physiotherapist. The control group received standard care. Main measures: The primary outcome, in this secondary analysis, was Motor Assessment Scale items 6, 7, and 8. Secondary outcomes were National Institute of Health Stroke Scale item 5, the Stroke Impact Scale domain 7, and the Modified Ashworth Scale in flexion/extension of the elbow. Results: In total, 380 persons with stroke were recruited, with mean (SD) age 72 (11) years, and baseline scores total National Institute of Health Stroke Scale was 1.4 (2.2)/1.6 (2.4) and Motor Assessment Scale items 6, 7 and 8 in the intervention/control group was 5.5 (1.2)/5.5 (1.2), 5.4 (1.4)/5.4 (1.3), and 3.6 (2)/3.5 (2), respectively. There was no significant difference between groups in terms of upper limb function in any of the Motor Assessment Scale items. In this population with minor stroke, upper-limb activity was good at three months post-stroke (74% of the maximum) and remained good 18 months later (77% of maximum). Conclusion: After intervention, there was no difference between the groups in terms of upper-limb activity.